2012 IEEE 23rd International Symposium on Personal, Indoor and Mobile Radio Communications - (PIMRC) 2012
DOI: 10.1109/pimrc.2012.6362504
|View full text |Cite
|
Sign up to set email alerts
|

Efficient wireless scheduling with limited channel feedback and performance guarantees

Abstract: It is well known that Max-Weight scheduling provides queue stability whenever this is possible. However, MaxWeight scheduling requires the complete channel state information (CSI) to make the best transmission decision at every time slot. The common assumption in this line of research assumes that the network controller has full CSI at every decision time without taking into account the overhead associated with channel probing. In practice, however, acquiring CSI is not cost-free and requires certain amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Z kn (t) = 1 if user k is scheduled on channel n at time slot t and zero otherwise). As mentioned in the Introduction, we will compare our scheme with the scheme of [13] applied in multiple carriers (will be referred to as "SSF" in the rest of the paper, standing for "Selective Scheduling and Feedback" [12], [13]). Variables with a tilde will be the quantities corresponding to the proposed scheme, while variables denoted with normal letters will correspond to the SSF scheme.…”
Section: Definition 1 (Stability Region) the Stability Region λ Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…Z kn (t) = 1 if user k is scheduled on channel n at time slot t and zero otherwise). As mentioned in the Introduction, we will compare our scheme with the scheme of [13] applied in multiple carriers (will be referred to as "SSF" in the rest of the paper, standing for "Selective Scheduling and Feedback" [12], [13]). Variables with a tilde will be the quantities corresponding to the proposed scheme, while variables denoted with normal letters will correspond to the SSF scheme.…”
Section: Definition 1 (Stability Region) the Stability Region λ Of Amentioning
confidence: 99%
“…Based on optimal stopping theory and assuming that the distributions of the channel gains are known to the base station, the authors derive the general properties of the centralized optimal probing policy and completely characterize it in some special cases. Finally, for the same model, the authors in [12], [13] have recently propose a simple feedback scheme for a single channel system. This scheme requires no knowledge of channel and traffic statistics and is shown to guarantee greater stability region than a scheme where all channels are probed.…”
Section: Introductionmentioning
confidence: 99%
“…In their seminal work, Tassiulas and Ephremides have shown that opportunistic Max-Weight algorithm which schedules the user with the highest queue backlog and transmission rate product at every time slot can stabilize the network, whenever this is possible [2]. This scheme has been generalized to wireless Preliminary version of the paper was presented at the International WDN Workshop on Cooperative and Heterogeneous Cellular Networks (WDN-CN2012) co-located with IEEE PIMRC in Sydney, Australia on Sep. 2012 [1].…”
Section: Introductionmentioning
confidence: 99%
“…This value is then sent back to the base station via the reverse link data rate request channel (DRC). The channel state information is 4 bits long and it is sent back every 1.67 ms 1 . If there are 25 users in a cell, 100 bits of channel state information is sent back to the base station every 1.67 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Different limitations result in such incomplete information, such as estimation error, delay and limited feedback resources, so it is important to analyze the impact of such imperfections on the system stability. For a single channel system, mainly time-division duplex (TDD), the authors in [11], [12] have proposed a feedback allocation scheme. Specifically, this scheme sets as threshold the rate of the user with the maximum queue length and requires no knowledge of channel and traffic statistic.…”
mentioning
confidence: 99%